EUGLYCE MIC DIABETIC KETOACIDOSIS WITH REFRACTORY METABOLIC ACIDOSIS IN A PATIENT WITH T2 DM ON EMPAGLIFLOZIN AND INTERMITTENT FASTING - Vicencio , Maria Roselle; Uy-Canto, Abigail (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Euglycemic Diabetic Ketoacidosis (EuDKA) is a clinical triad of normal blood glucose levels, ketonemia, and high anion gap metabolic acidosis. It is less commonly associated with the use of Sodium-Glucose Co-Transporter 2 inhibitors (SGLT2i) such as empagliflozin. Due to the introduction of SGLT2i in the treatment of T2DM and HF, there is an increasing incidence of EuDKA. CASE We report a case of a 28-year-old female recently diagnosed with diabetes mellitus type 2 (T2 DM) maintained on semaglutide 0.25 mcg subcutaneously once a week and empagliflozin 10 mg once daily presenting with a threeweek history of easy fatigability, generalized body weakness, nausea, vomiting and loss of appetite. At the ER, the patient experienced abdominal pain, nausea, and vomiting. The patient was managed as a case of severe refractory metabolic acidosis secondary to EuDKA. The patient was intubated for 5 days. The management consisted of insulin drip, hydration, renal replacement therapy (RRT), and bicarbonate drip. Resolution of acidosis with a pH of 7.42 and anion gap of 10.1 was achieved on the 8th day of admission. CONCLUSION This case reports a rare complication of SGLT2i in a patient with T2DM with retractable severe metabolic acidosis that can be effectively managed with RRT and cessation of SGLT2i. It also highlights the importance of giving D5- containing IV fluid for continued insulin administration which is important to reverse ketoacidosis while preventing hypoglycemia. Monitoring of serum ketones and serum electrolytes levels are crucial in the management of a patient with intractable acidosis needing mechanical ventilation and renal replacement therapy.